PERBANDINGAN EKSTRAKSI AKAR KUCING (ACALYPHA INDICA L.) DENGAN EKSTRAK ETANOL 96% DAN EKSTRAK AKUADES TERHADAP PERTUMBUHAN EPEC DAN CANDIDA ALBICANS - M. Guli, Musjaya; Zahra, Yuyun Jannatul; Ardiputra, Muh. Akbar; Toemon, Agnes Immanuela (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
The root of the cat (Acalypha indica L.) was used as the object of research and extraction was carried out to determine the antimicrobial activity of 96% ethanol extract and distilled water against EPEC (Enterophatogenic Escherichia coli) bacteria and the fungus Candida albicans. The method used for plant sampling is purposive sampling method. Extraction of active compounds using maceration method. The antimicrobial potency test used the agar-diffusion method using two types of microbial pathogens, namely the bacteria EPEC and the fungus Candida albicans. Each paper disk was given 50 µL of bacterial isolate, incubated at 37 0C for 24 hours and continued for 48 hours. The observed parameter is the clear zone formed around the paper disk. The results showed that cat root (A. indica L.) contains compounds that can inhibit the growth of EPEC bacteria and the fungus C. albicans. A good solvent to extract the active compounds contained in the cat root plant (A. indica L.) is distilled water. Treatment with aquadest extract with a concentration of 100% had the widest inhibition zone among other treatments, namely 6.8 mm against the growth of EPEC bacteria and ethanol extract with a concentration of 100% which was 3.8 mm against the growth of the fungus Candida albicans.